Transgender Athletes and Title IX Compliance (Higher Education Politics and Economics, 2025)
This opinion piece examines the complex issue of transgender athletes in college sports, focusing on recent federal policy changes and their implication for Title IX compliance. The article highlights the tension between inclusive policies and concerns about competitive fairness, while noting the lack of data on transgender athlete participation. Anecdotal estimates suggest that the number of transgender athletes in college sports is incredibly small, suggesting that the issue may receive disproportionate attention compared to more widespread challenges in college sports. The article argues that while the debate over transgender participation is significant, it should not overshadow persistent issues such as widespread noncompliance with Title IX standards for women’s athletics. The article calls for a balanced approach that addresses systemic inequities affecting a larger number of student athletes.